Market Access Maps Database (MAcMap-HS6) - International Trade Center; United Nations Conference on Trade and Development; World Trade Organization; Centre d'Etudes Prospectives et d'Informations Internationales; International Food Policy Research Institute (International Food Policy Research Institute, 2009)
As trade negotiations increasingly rely on quantitative assessments, tariff information becomes necessary in shedding light on applied protection at a detailed level. The purpose of such information is not only to provide a measure of border protection, but also to pave the way for well-suited economic analysis of the consequences of trade liberalization, in particular through CGE models. The MAcMapHS6 project has been developed to answer these needs. A joint effort of the International Trade Center (ITC), a cooperation agency of United Nations Conference on Trade and Development (UNCTAD), World Trade Organization (WTO), Geneva), Centre d'Etudes Prospectives et d'Informations Internationales (CEPII, Paris) and International Food Policy Research Institute (IFPRI), led to the development of the first version of a Market Access Maps database (MAcMapHS6-v1) (Bouët et al, 2008), the purpose of which was mainly to provide protection figures for the 6th release of the GTAP database (Bouët et al, 2005). The first version of MAcMapHS6 represents an unprecedented effort to monitor worldwide border protection at the most detailed level, while accounting exhaustively for preferential trade agreements. This effort has been pursued with the development of an updated version of this database (MAcMapHS6-v2) relying on 2004 data. Methodology and data quality have been improved. The new database provides evidence on the world applied protection in 2004. MAcMapHS6-v2 is also the source of protection data for both the GTAP7 database and the TASTE software. Its main contributions are: (i) an exhaustive coverage of preferential trade arrangements across the world; (ii) the calculation of the ad valorem equivalent (AVE) for specific duties, acknowledging the differentiated impact of such duties across exporters, depending on their export unit values; (iii) the incorporation of tariff-rate quotas both through the AVE of the resulting protection at the margin, and through the calculation of involved rents; (iv) an original aggregation methodology, using a weighting scheme based on reference groups of countries, and limiting the extent of the endogeneity bias inherent to the standard, import-weighted average protection.